Towards super-clean graphene - Li Lin (Nature Portfolio, 2019)
The intrinsic properties of graphene and the resulting device performance are hindered by the impurities produced during the synthesis process. Here, the authors elucidate the origin of contaminations in CVD-grown graphene and devise a strategy towards the scalable production of ultra-clean graphene with >99% clean regions and low contact resistance.